Targeting Human Immunodeficiency Virus Type 1 Assembly, Maturation and Budding - Wapling, Johanna (Libertas Academica, 2007)
The targets for licensed drugs used for the treatment of human immunodeficiency virus type 1 (HIV-1) are confined to the viral reverse transcriptase (RT), protease (PR), and the gp41 transmembrane protein (TM). While currently approved drugs are effective in controlling HIV-1 infections, new drug targets and agents are needed due to the eventual emergence of drug resistant strains and drug toxicity. Our increased understanding of the virus life-cycle and how the virus interacts with the host cell has unveiled novel mechanisms for blocking HIV-1 replication. This review focuses on inhibitors that target the late stages of virus replication including the synthesis and trafficking of the viral polyproteins, viral assembly, maturation and budding. Novel approaches to blocking the oligomerization of viral enzymes and the interactions between viral proteins and host cell factors, including their feasibility as drug targets, are discussed.